OPEN LEADERSHIP MODEL IN DEVELOPMENT BASED ON CITIZENSHIP IN CONDONGCATUR KALURAHAN - Nuryanto Nuryanto (Bajang Institute, 2023)
The research aims to determine the open leadership model in community development bBased on the Rukun Warga (RW) case study in the Condongcatur sub-district, Kapanewon, Depok, district Sleman Special Region of Yogyakarta. RW-based development as a form of transformation from ppadukuhan or village-based development. The realization of RW-based development in The Condongcatur Village Head because the Condongcatur Village Head has led the implementation of the village administration open leadership model, so that society andstakeholder can receive with offset the very high turnout. Single case study qualitative research approach,Data collection techniques were carried out by interviews, observation and documentation. The data analysis technique follows Creswell (2016), informance is determined by propursiv sampling.The research results showopen leadership model in community development bbased on RW in the Condongcatur sub-district, Kapanewon, Depok, Sleman district, Special Region Yogyakarta was born as a transition from village/village-based community development. The community development strategy based on hamlets becomes RW-based development, shows that village-based development has failed, because of development community-based community groups have to wait a long time, are not fair and participatory low society. While the RW-based community development is very community participation high, the waiting period is short and justice is served quickly. Implementation of development based RW can be seen in the leadership of a village head who is very open, both open horizontally, vertical and diagonal. An advanced and developing village cannot be separated from the role of a village head in leading the people.